PRO*MDD Study Protocol: Effectiveness of Outpatient Treatment Programs for Major Depressive Disorder: Metacognitive Therapy vs. Behavioral Activation a Single-Center Randomized Clinical Trial - Schaich, Anja; Heikaus, Laura; Assmann, Nele; Köhne, Sandra; Jauch-Chara, Kamila; Hüppe, Michael; Wells, Adrian; Schweiger, Ulrich; Klein, Jan Philipp; Fassbinder, Eva (Frontiers in Psychiatry, 2018)
Abstract Background: Major depressive Disorder (MDD) is a severe mental disorder associated with considerable disability and high costs. Over the last decades, various psychotherapies for MDD have been developed and researched, among others Behavioral Activation (BA) and Metacognitive Therapy (MCT). MCT and BA target different maintaining factors of MDD and have not been compared to date. The PRO*MDD randomized controlled trial will compare MCT and BA in the routine clinical setting of an outpatient clinic. Methods and Design: We aim to recruit 128 MDD patients, who will be randomly assigned to either MCT or BA after a naturalistic waiting time. In both conditions, patients will receive one individual therapy session and one group therapy session per week for a maximum of six months. Assessments will take place at baseline, pre-treatment, mid-treatment, post-treatment as well as at 12 months, 18 months and 30 months after start of treatment as follow-up. The primary outcome is reduction of depression severity; secondary outcomes address quality of life, psychosocial functioning and participation as well as comorbidity. Discussion: The PRO*MDD study is the first randomized controlled trial to compare the effectiveness of MCT and BA. The outcome of this trial will increase our knowledge on the effectiveness and applicability of both treatment modalities and therefore contribute to the improvement of treatment for depressive patients. Trial registration: German Clinical Trials Register DRKS-ID: DRKS00011536 (retrospectively registered)